2018
DOI: 10.1523/jneurosci.2219-18.2018
|View full text |Cite
|
Sign up to set email alerts
|

Neurochemical and Behavioral Dissections of Decision-Making in a Rodent Multistage Task

Abstract: Flexible decision-making in dynamic environments requires both retrospective appraisal of reinforced actions and prospective reasoning about the consequences of actions. These complementary reinforcement-learning systems can be characterized computationally with model-free and model-based algorithms, but how these processes interact at a neurobehavioral level in normal and pathological states is unknown. Here, we developed a translationally analogous multistage decision-making (MSDM) task to independently quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 29 publications
0
39
0
Order By: Relevance
“…A number of reports have now been published evaluating two-stage discrimination learning in rodents (Akam et al, 2015;Miller et al, 2017;Groman et al, 2019). In a recent study, using a task modeled on that described for use in humans above, we sought to investigate how the state-space and action representations adapt to the structure of the world during the course of learning without any explicit instructions about the structure of the task -which obviously cannot be provided to rats (Dezfouli and Balleine, 2019) -see Figure 2E.…”
Section: Rodentmentioning
confidence: 99%
“…A number of reports have now been published evaluating two-stage discrimination learning in rodents (Akam et al, 2015;Miller et al, 2017;Groman et al, 2019). In a recent study, using a task modeled on that described for use in humans above, we sought to investigate how the state-space and action representations adapt to the structure of the world during the course of learning without any explicit instructions about the structure of the task -which obviously cannot be provided to rats (Dezfouli and Balleine, 2019) -see Figure 2E.…”
Section: Rodentmentioning
confidence: 99%
“…A recent F-DOPA PET-fMRI study showed that individuals with higher ventral striatal DA synthesis capacity, indicating higher baseline DA [13], exert more reliance on MB than MF control, show stronger MB learning signals in the lateral prefrontal cortex (PFC) and weaker ventral striatal (VST) MF learning signals [8]. Using a rodent version of the same task, a positive correlation between baseline VST DA and MB control was recently confirmed [14]. Taken together, whereas the relationship to MF control remains unclear, a positive relationship between higher baseline DA and more MB control is supported by a series of human studies and one recent animal study.…”
Section: Introductionmentioning
confidence: 93%
“…Developing rodent versions of the two‐step task is necessary for dissecting the neural circuits of model‐based and model‐free control. Currently four different versions of the task (Akam et al, ; Groman, Massi, Mathias, Curry, et al, ; Hasz & Redish, ; Miller, Botvinick, & Brody, ) have been described that differ from the human versions of the task in several important ways. Two of these tasks—one in mice (Akam et al, ) and the second in rats (Miller et al, ; Miller, Botnivick et al, )—do not have a second step choice.…”
Section: Two‐step Decision‐making Tasks—a Powerful Solutionmentioning
confidence: 99%
“…A first step choice leads to a second step state, signaled via an illuminated nose poke, which leads to a probabilistic reward. However, the third and fourth tasks, in rats, maintain a second step choice (Groman, Massi, Mathias, Curry, et al, ; Hasz & Redish, ). The second main difference between rodent and human tasks involves how reward probabilities vary between trials.…”
Section: Two‐step Decision‐making Tasks—a Powerful Solutionmentioning
confidence: 99%